STANDARDIZATION OF FACILITIES AND INFRASTRUCTURE BASED ON ISO 9001:2015 (CASE STUDY OF ATTAQWA PUTRA ISLAMIC BOARDING SCHOOL-BEKASI) - Nijan, Mirwan; Warto, Priawon Cendra; Gunawan, Peri; Yasir, Muhamad; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to understand the development of facilities and infrastructure at the At Taqwa Putra Islamic Boarding School.** This research uses a descriptive qualitative approach with interactive or case study methods. Data collection techniques employed include interviews, observation, and document studies supporting the research. The study findings indicate that At Taqwa Putra Islamic Boarding School has a facility management and maintenance program called BSA (Clean Under One Roof). This program manages all facilities at At Taqwa Putra, including those at the Madrasah Ibtidaiyah, Madrasah Tsanawiyah, and Madrasah Aliyah. To support this program, the boarding school has established a BSA team consisting of 20 staff members and 2 managers. In addition, At Taqwa has other facilities such as sports fields, science laboratories, computer labs, libraries, and other amenities.